Design, analysis and fabricate of automatic noodle making machine / Azril Firdaus Azmi and Ahmad Faidzal Khodori - Azmi, Azril Firdaus; Khodori, Ahmad Faidzal (School of Mechanical Engineering, 2022)
Noodles are a high demand food item required in a variety of dishes including chowmein, hakka noodles, and a variety of dishes. Preparation of noodles from batter is a tiring process and difficult to do by hand. Depending on the high demand, the supply of noodles requires a tireless process to keep up with the huge demand. The process is tiring so that people stop doing it. The main objective of this project is to design and fabricate the noodle making machine that helps people to create their own noodles and can cut more noodles within a short time. The methodologies that are used are preparing 3 design sketches and choosing the best out of 3. Then, make engineering calculations with the dimensions selected and draw a project in Solidworks to make engineering analysis. The cost is calculated. Project expected to be a nice machine and can help to make noodles